2014
DOI: 10.1507/endocrj.ej13-0369
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25(OH)D and vitamin D status in relation to <i>VDR</i>, <i>GC</i> and <i>CYP2R1</i> variants in Chinese

Abstract: Vitamin D status, measured by 25-hydroxyvitamin D [25(OH)D], is important for musculoskeletal and non-musculoskeletal health. Vitamin D deficiency has been related to rickets, diabetes mellitus, metabolic syndrome, hypertension, cardiovascular disease, and cancer [1][2][3][4][5][6]. Sun exposure, dietary and supplementary vitamin D intake, race, age, sex, obesity, skin color, and tea intake have been previously reported to be associated with circulating levels of 25(OH)D [7][8][9][10] Chinese. Nine common vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 39 publications
7
27
2
Order By: Relevance
“…There is one study carried out in Chinese population. Li et al recruited 1,443 unrelated employees and retired workers from a factory in Dali (25°N), Yunnan Province, China [39]. After LD analysis of rs4588 and rs7041, the disequilibrium coefficient ( r 2 = 0.16) was really close to our result.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There is one study carried out in Chinese population. Li et al recruited 1,443 unrelated employees and retired workers from a factory in Dali (25°N), Yunnan Province, China [39]. After LD analysis of rs4588 and rs7041, the disequilibrium coefficient ( r 2 = 0.16) was really close to our result.…”
Section: Discussionsupporting
confidence: 82%
“…To our best knowledge, there are no correlative literatures about genetic linkage of these two sites. However, GC rs4588 and rs7041 are reported to be linked together in several studies [3943]. Genetic distribution and transmission vary from race to race.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been suggested that the polymorphisms of GC (also known as VDBP ), CYP2R1 and DHCR7/NADSYN1 genes might contribute to interpersonal variability in the serum 25(OH)D levels of Chinese, it is also suggested that only a few common variants of the GC gene are genetic determinants of low serum levels of vitamin D in Chinese . Similarly, studies of Arabs and South Asians have found a positive relationship between vitamin D insufficiency with polymorphisms in GC and CYP2R1 genes .…”
Section: Future Researchmentioning
confidence: 99%
“…VDR , the superfamily of transacting transcriptional regulatory factors, adjusts to several gene transcriptions, including cell apoptosis, pro-oncogenes, immunomodulation, differentiation, and tumor-suppressor genes [9,10]. The vitamin D-binding protein (encoded by the group-specific component , GC gene) mainly promotes transportation of vitamin D metabolites [11].…”
Section: Introductionmentioning
confidence: 99%